How to implement a robust BCDR plan. Issue 7 (July 2019) - Weeks, Ryan
Abstract : Ransomware remains a problem and businesses in Europe are now suffering more from ransomware attacks than their global counterparts. For example, a recent survey among managed service providers (MSPs) found that 42% of European MSPs saw their small and medium-sized clients suffer multiple attacks in a single day. 1 This was higher than the global average of 35%. Ransomware remains a problem and businesses in Europe are now suffering more from ransomware attacks than their global counterparts. Such attacks can be crippling and are spreading to the cloud. It is essential for organisations to implement a solid business continuity and disaster recovery (BCDR) plan to minimise any risk of system downtime and loss of sensitive information, but they should also be aware there is no single 'right' approach, explains Ryan Weeks of Datto.